2009
DOI: 10.1523/jneurosci.3854-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Functional Reorganization of Retinal Circuits Induced by Early Long-Term Visual Deprivation

Abstract: Early sensory experience shapes the functional and anatomical connectivity of neuronal networks. Light deprivation alters synaptic transmission and modifies light response properties in the visual system, from retinal circuits to higher visual centers. These effects are more pronounced during a critical period in juvenile life and are mostly reversed by restoring normal light conditions. Here we show that complete light deprivation, from birth to periods beyond the critical period, permanently modifies the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 65 publications
(79 reference statements)
0
34
0
Order By: Relevance
“…Previous results in cat and monkey suggest that cortical changes occur independently of effects on retina (Hendrickson and Boothe, 1976; Sherman and Stone, 1973). Results reported here raise the possibility that effects of light deprivation on the development of mouse visual cortex, retinogeniculate projections (Hooks and Chen, 2006), and retinal amacrine and ganglion cells (Di Marco et al, 2009; Giovannelli et al, 2008; Tian and Copenhagen, 2001; 2003; Vistamehr and Tian, 2004) could relay changes from earlier stages of processing. Previous reports demonstrate that dark rearing disrupts the normal developmental increase in synaptic inputs to ganglion cells (Tian and Copenhagen, 2001).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Previous results in cat and monkey suggest that cortical changes occur independently of effects on retina (Hendrickson and Boothe, 1976; Sherman and Stone, 1973). Results reported here raise the possibility that effects of light deprivation on the development of mouse visual cortex, retinogeniculate projections (Hooks and Chen, 2006), and retinal amacrine and ganglion cells (Di Marco et al, 2009; Giovannelli et al, 2008; Tian and Copenhagen, 2001; 2003; Vistamehr and Tian, 2004) could relay changes from earlier stages of processing. Previous reports demonstrate that dark rearing disrupts the normal developmental increase in synaptic inputs to ganglion cells (Tian and Copenhagen, 2001).…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, several studies have examined excitatory and inhibitory circuits in visual cortex following monocular deprivation and have found that inhibitory circuits are altered even when excitatory circuits are not (Chen et al, 2012; van Versendaal et al, 2012; reviewed in Espinosa and Stryker, 2012). Within the retina, dark rearing caused an imbalance of excitatory and inhibitory inputs to ganglion cells (Di Marco et al, 2009). At the first synapse examined here, the differences in timing and strategies of choosing presynaptic partners by the type 6, 7, and 8 ON cone bipolar cells (Dunn and Wong, 2012) also emerged in the effects of dark rearing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of light exposure during development of the visual system has been extensively studied, demonstrating that modifications of visual input or its deprivation result in differential outcomes in brain structure and function [1][6]. Here we report the findings on the effects of prenatal auditory stimulation at a higher sound pressure level on the development of hippocampus of neonatal chick at biochemical and behavioral level.…”
Section: Introductionmentioning
confidence: 80%
“…However, the generally high level of responsiveness observed in the visual cortex after darkness rules out the possibility that the blindness results from a loss of retinal function owing to darkness. Although the effects of darkness on retinal function have not been studied in cats, a study on rats [18] revealed long-lasting changes of retinal ganglion cell organization in animals reared for very long periods in darkness from birth to four months of age. On the other hand, there is a growing realization [19,20] that various forms of selected visual deprivation exert substantial effects beyond the striate cortex, and so it is possible that the behavioural consequences of the short periods of darkness are rooted in these widespread events in other interconnected cortical areas.…”
Section: Discussionmentioning
confidence: 99%